Implicações fisiológicas do uso do óleo essencial de Lippia alba, quimiotipos linalol e citral, na anestesia de Rhamdia quelen - Souza, Carine de Freitas (2018)
Recently, it was reported that the Lippia alba essential oil (EO) linalol chemotype causes anesthesia in fish of Rhamdia quelen species. However, it is known that a given vegetal species can present differences in its chemical composition, which varies according to the chemotype, local of sampling, time of year and type of soil. In this way, it is necessary a cautious investigation to determine whether anesthetic and sedative effects of L. alba EO are maintained at different chemotypes, as well as to analyze their effects on fish physiology before recommending it as a safe anesthetic. The present study evaluated the blood, plasmatic and biochemical effects caused from anesthesia with two different chemotypes of L. alba EO: linalol (EO-L) and citral (EO-C) in R. quelen. In the first experiment the concentrations of 100 and 300 μL/L were used to anesthetize the fish. Blood was collected through anesthesia and recovery in order to investigate the ionic, blood and biochemical parameters. The plasma Na+, K+ and Ca2+ levels did not show alterations during anesthesia induction and recovery with both treatments. However, blood glucose increased during anesthesia with both anesthetics. Plasmatic creatinine levels increased at the end of recovery in fish anesthetized with EO-C. In this sense, a second experiment was carried out in order to verify whether the alterations observed in the first experiment could be indicative of tissue damage. Thus, the aim of the second experiment was to investigate the effects of anesthesia on biochemical, antioxidant and tissue damage parameters, replicating the same experimental model used previously. As result, it was observed that although anesthesia with EO-C and EO-l avoided the increase on plasma cortisol levels, EO-C increased thiobarbituric reactive acid substances, as well as protein carbonylation in liver and kidney of fish. On the other hand, EO-L did not cause any type of tissue damage. Thus, this study proves that different chemotypes of a given vegetal species can provoke different physiological effects. In summary, we recommended the use of EO-L as an effective and safe anesthetic to R. quelen.